Chemical Composition, Antimicrobial and Insecticidal Activities of Essential Oils of Discarded Perfume Lemon and Leaves (Citrus Limon (L.) Burm. F.) as Possible Sources of Functional Botanical Agents - Wu, Panpan; Tang, Xiaowen; Jian, Rongchao; Li, Jiahao; Lin, Maoyu; Dai, Huachao; Wang, Kangpeng; Sheng, Zhaojun; Chen, Baizhong; Xu, Xuetao; Li, Chen; Lin, Zhongze; et al. (Frontiers in Chemistry, 2021)
Two essential oils were isolated from discarded perfume lemon and leaves (Citrus limon (L.) Burm. F.) by hydro-distillation with good yield (0.044% for perfume lemon and 0.338% for leaves). Their biological activities were evaluated against five selected bacterial strains and Aedes albopictus (Ae. albopictus, Diptera: Culicidae). Chemical composition indicated that both essential oils were rich in essential phytochemicals including hydrocarbons, monoterpenes and sesquiterpene. These constituents revealed some variability among the oils displaying interesting chemotypes (R)-(+)-limonene (12.29–49.63%), citronellal (5.37–78.70%) and citronellol (2.98–7.18%). The biological assessments proved that the two essential oils had similar effect against bacterial (inhibition zones diameter ranging from 7.27 ± 0.06 to 10.37 ± 0.15 mm; MICs and MBCs ranging from 1.6 to 6.4 mg/mL); against Ae. albopictus larvae (LC50 ranging from 384.81 to 395.09 ppm) and adult mosquito (LD50 ranging from 133.059 to 218.962 μg/cm2); the activity of the two chemotypes ((R)-(+)-limonene and citronellal): larvae (LC50 ranging from 267.08 to 295.28 ppm), which were all presented in dose-dependent manners. Through this work, we have showcased that recycling and reusing of agriculture by-products, such as discarded perfume lemon and leaves can produce eco-friendly alternatives in bacterial disinfectants and mosquito control product.